POTENSI LESTARI DAN MUSIM PENANGKAPAN IKAN KURISI (Nemipterus sp.) YANG DIDARATKAN PADA PELABUHAN PERIKANAN NUSANTARA SUNGAILIAT - Juandi Juandi; Eva Utami; Wahyu Adi (Akuatik: Jurnal Sumberdaya Perairan, 2016)
Threadfin Bream (Nemipterus sp.) became the main commodity because has high economic value in Bangka. The purpose of the study are to analyze Maximum Sustainable Yield (MSY), to determine fishing season and to Maximum Economic Yield (MEY). This research was done from January to April 2015, in Pelabuhan Perikanan Nusantara Sungailiat. Data collected include fishing activity (questionnaire), income, catch and effort from 2005 to 2013. The results showed that slope (b) is still positive, it means the resources are still abundant and overfishing has not happened yet. Fishing season occurred in February (102.972%), March (126.315%), April (134.570%), Mei (119.313%), June (109.783%), July (107.789%), and October (100.518% ). Maximum Economic Yield (MEY) Estimation is 4.837.513 kg / year and Effort of Maximum Economic Yield (FMEY) is 183.038 trips / year.